2021
DOI: 10.3390/nu13082882
|View full text |Cite
|
Sign up to set email alerts
|

Edible Plant Sprouts: Health Benefits, Trends, and Opportunities for Novel Exploration

Abstract: The consumption of plant sprouts as part of human day-to-day diets is gradually increasing, and their health benefit is attracting interest across multiple disciplines. The purpose of this review was to (a) critically evaluate the phytochemicals in selected sprouts (alfalfa, buckwheat, broccoli, and red cabbage), (b) describe the health benefits of sprouts, (c) assess the recent advances in sprout production, (d) rigorously evaluate their safety, and (e) suggest directions that merit special consideration for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 175 publications
0
26
0
1
Order By: Relevance
“…Growing sprouts is a cheap and easy process that does not require sophisticated equipment and that provides high yields. All of these features make sprouts from different botanic families alternative sources of phytoconstituents and minerals, important for human health [3,[15][16][17][18]. Moreover, sprouts can be grown all year round, at home, and they reach maturity in most cases within 5 to 14 days, depending on the crop nature and botanical origin [16].…”
Section: Introductionmentioning
confidence: 99%
“…Growing sprouts is a cheap and easy process that does not require sophisticated equipment and that provides high yields. All of these features make sprouts from different botanic families alternative sources of phytoconstituents and minerals, important for human health [3,[15][16][17][18]. Moreover, sprouts can be grown all year round, at home, and they reach maturity in most cases within 5 to 14 days, depending on the crop nature and botanical origin [16].…”
Section: Introductionmentioning
confidence: 99%
“…Поэтому актуальным является проведение исследований по изучению влияния условий проращивания на изменение микрофлоры как фактора безопасности пищевых продуктов из пророщенного зерна. Учеными разных стран подробно изучено влияние микробной активности на аспекты микробиологической безопасности и качества зерна [2][3][4][5]. Микрофлора зерна сосредоточена во внешних слоях зерна и внутри зародыша [6,7].…”
Section: Introductionunclassified
“…Sprouted seeds have long been consumed in oriental countries and form an important part of their culinary history. Given their rich flavour, smell and bioactive compounds, these products can be used to prepare salads or other high-quality foods, and positive perceptions of these products have influenced the development of foods such as breakfast cereals, snacks and baked goods [ 5 ]. However, although there are new options for the consumption of sprouts and a large proportion of the population prefers healthy foods and is inclined to consume them, several studies have reported that the selection and perception of healthy foods could be related to several sociodemographic characteristics of the population [ 6 ].…”
Section: Introductionmentioning
confidence: 99%